Viabilidade da produção de Gypsophila paniculata à campo na latitude 28ºS - Paiz, Carla Marina Borges (2020)
The entire Brazilian territory allows the floriculture production, both for the variability of climates and the high availability of genetic materials. However, it’s necessary reconcile the best genotypic expression in the most suitable location for it, especially when cultivation is made in open sky style. In the case of gypsophila, to flower it depends on high average temperatures and long day length. This work aimed to evaluate the development of Gypsophila paniculata seedlings arising from in vitro cultivation in field cultivation at latitude 28º S in summer. The experiment was conducted in the field, in the UPF agrobiodiversity garden on an elevated flower bed with a 10 cm layer of dry leaves, from December 2019 to May 2020. In the management efficient microorganisms (EM) were used in the management in initial fortnightly applications. Plant survival, height and number of inflorescences produced were evaluated (mean and standard deviation) the presence of hares was observed in the experimental field at the end of the first month of the experiment. Plants with 27 cm in height and 22.8 in diameter, bloomed at 76 days after transplantation (DAT) Shoots were recorded at 45 DAT. With a final survival of 9.2% of the seedlings planted, the damage by hares was verified. It is concluded, since the action of vertebrate predators is controlled, the production of Gypsophila in the field in raised flower beds is feasible, at latitude 28ºS in summer with drought.